Inter‐laboratory comparison of UV‐light sources for testing of PV‐modules. (28th April 2015) - Koehl, Michael; Philipp, Daniel
Abstract: Durability assessment of materials exposed to natural weathering requires accelerated testing for verification of the ultraviolet (UV) stability, especially for polymeric material. The type approval testing of photovoltaic (PV) modules according to the standards International Electrotechnical Commission (IEC) 61215 and IEC 61646 includes a so‐called UV‐preconditioning test with a total UV dose of 15 kWh/m 2 corresponding to natural weathering of about 3 months only. A serious UV test representing the service life needs to apply a much stronger UV‐intensity in a comparable way. Fraunhofer Institute for Solar Energy Systems performed an inter‐laboratory comparison of UV‐light sources in 13 accredited test labs and test centres of major PV module manufacturers. The most important topic was the spectral radiometric measurement of the used UV sources. Another main issue was the comparison with the integral measurements by the sensors used for control of the tests. Errors up to 120% were found. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Durability assessment of materials exposed to natural weathering requires accelerated testing for verification of the ultraviolet (UV) stability, especially for polymeric material. Fraunhofer Institute for Solar Energy performed an inter‐laboratory comparison of UV‐light sources in 13 accredited test labs and test centres of major PV module manufacturers in order to evaluate the differences of the used UV‐sources and sensors by spectral radiometric measurement.